Hodnocení finanční situace podniku a návrhy na její zlepšení - Karpíšková, Marcela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Úkolem této diplomové práce je zhodnocení finančního zdraví společnosti Pilkington Czech, s.r.o., prostřednictvím vybraných metod finanční analýzy. Obsahuje návrhy možných řešení zjištěných problémů, které mají vést ke zlepšení finanční situace podniku v budoucích letech.

The objective of this thesis is evaluation of financial health of Pilkington Czech s.r.o. by using chosen methods of financial analysis. It contains concepts of potential solutions of discovered problems, which have to lead in the future to the improvements of financial situation of the company.
Evaluation of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: Finanční analýza; metody finanční analýzy; poměrové ukazatele; rozdílové ukazatele; soustavy ukazatelů; SWOT analýza; rozvaha; výkaz zisku a ztráty.; Financial analysis; Methods of financial analysis; Ratio indexes; Diferential ratio; Ratio systems; SWOT analysis; Balance sheet; Profit and loss report.